Riesgos a la salud por la contaminación radioactiva del agua potable de la ciudad de Riobamba - Guevara Cruz, Susana Cristina (2015)
Risks to health by the radioactive contamination of drinking water for the city of Riobamba were analyzed through a radiological study in the Laboratory of Environmental Radioactivity Monitoring and Control Secretariat for Nuclear Applications during 2014. For the determination of radioactive contamination use d two techniques, the first, total alpha and beta for evaporation method , was obtained a total alpha activity of 0.1 Becqu erel per liter (BqL - 1 ) and 1 Becquerel per liter (BqL - 1 ) for total beta and 0.08 milisieverts (mSv) for total annual effective dose . Th e second technique, the gamma spectromet ry for a concentrated sample, through was detected radionuclides alpha and beta emitters in drinking water. The drinking water of the city of Riobamba does not exceed the limits regulated by the World Health Organiza tion, 0.5 Becquerel per liter (B q L - 1 ) to the to tal alpha activity and 1 Becquerel per liter (B q L - 1 ) beta activity overall, from the radiological point of view it is suitable and safe for human consumption, so it is not a risk to the health of the population.